TRAINING AND ASSISTANCE OF ONLINE MARKETING OF PROCESSED MARINE PRODUCTS MICRO-MEDIUM BUSINESS “LAMORA” IN KAUMAN VILLAGE, SOCAH, BANGKALAN - Taufik; Indah Werdiningsih; Faried Effendy; Nania Nuzulita; Ibaneza Griffint Secoria; Aulia Marcha Rizkasari Putri (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
Lamora is a cracker and petis industry located in Kauman village, Socah sub-district, Bangkalan district, which has become a pilot MSME. Under the guidance of the Ministry of Industry and Manpower and the Department of Health of Bangkalan Regency, this MSME has had a website (https://kerupukikansocah.com) since 2017. Before the pandemic, Lamora only served orders and purchases directly from individuals or resellers from Bangkalan and its surroundings. However, during the Covid-19 pandemic, sales turnover decreased by more than 60%. This requires serious attention to maintain business continuity. The solution provided is a training and mentoring partnership program to provide MSME actors with the ability to use information technology (IT) as a marketing and sales medium, conduct online marketing on social media, manage online stores in market places and use promotional media design applications for free. The training which lasted for two days has gone well and has achieved the expected goal, namely increasing the understanding of Lamora MSME actors towards online marketing using IT.